Pengaruh Faktor Ekonomi Terhadap Jumlah Kejahatan (Crime Total) Di Indonesia (2015-2017) - Masfiatun, Masfiatun (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2019)
This study is motivated by the number of crimes in Indonesia in 2015-2017 that are fluctuating. Efforts and policies to prevent and reduce crime have been carried out by state in this case the security apparatus (Polri), but the implication is that not all regions can reduce the number of crimes. Therefore this study tries to examine whether economic factors influence the number of crimes. The model used in this study is a random effect model with a period of research from 2015 to 2017. The results of the study indicate economic inequality has a positive effect significant on the number of crimes, while the variables of economic growth, poverty, and unemployment do not affect significantly to the number of crimes.